Price and carbon emission decisions under pressures of consumer, regulator and competition. (2016) - Xiong, Yu; Yang, Jiaquan; Li, Yimeng
This paper examines the impacts of consumer environmental awareness, carbon emission tax and competition on the firms' economic and environmental performance. We find that both in the single-channel supply chain and dual-channel supply chain, the manufacturer in a 'clean' industry invests to reduce the amount of carbon emissions per unit of product produced actively; however, the manufacturer in a 'dirty' industry is expected to reject the environmental investment. The retailer is always better off with a higher consumer environmental awareness or a higher carbon emission tax in a 'clean' industry, but worse off in a 'dirty' industry. The manufacturer is better off with a higher consumer environmental awareness or a higher carbon emission tax if and only if she is in a 'dirty' industry and in the dual-channel supply chain. The numerical examples present the condition which secures Pareto gains after the manufacturer encroaches.